2017
DOI: 10.1080/01930826.2017.1360021
|View full text |Cite
|
Sign up to set email alerts
|

Dropped in Without a Parachute: Library Managers' Supervision Experiences

Abstract: A survey of U.S. library managers explored the relationship between their social identities, experiences supervising others, support from others, and their overall satisfaction in their professional role. The literature provides evidence that demographic differences give rise to challenges in the workplace. Though no statistically significant differences were found between minority and nonminority managers related to supervisees' microaggressive behaviors, written commentary provided evidence of these and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…When the perceptions of this study's respondents are considered, the results of both previous studies are consistent with the findings of the current study. Funge et al. (2017) surveyed academic libraries in the United States about the relationship between supervisors and supervisees.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the perceptions of this study's respondents are considered, the results of both previous studies are consistent with the findings of the current study. Funge et al. (2017) surveyed academic libraries in the United States about the relationship between supervisors and supervisees.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…When the perceptions of this study's respondents are considered, the results of both previous studies are consistent with the findings of the current study. Funge et al (2017) surveyed academic libraries in the United States about the relationship between supervisors and supervisees. The findings revealed that the supervisors' behaviour was motivated by a lack of opportunities for personal development and career advancement.…”
Section: Next-generation Leadershipmentioning
confidence: 99%
“…Communication skills, problem-solving, team building and conflict resolution are amongst the competencies highlighted by Funge et al (2017). The Library Leadership Management Association (LLAMA) identified these competencies in 2016.…”
Section: Leadership As Social Identitiesmentioning
confidence: 99%